Booming far: the long-range vocal strategy of a lekking bird - Cornec, C.; Hingrat, Y.; Aubin, T.; Rybak, F. (Royal Society open science, 2017)
The pressures of selection acting on transmission of information by acoustic signals are particularly high in long-distance communication networks. Males of the North African houbara bustard (Chlamydotis undulata undulata) produce extremely low-frequency vocalizations called ‘booms’ as a component of their courtship displays. These displays are performed on sites separated by a distance of on average 550 m, constituting exploded leks. Here, we investigate the acoustic features of booms involved in species-specific identity. We first assessed the modifications of acoustic parameters during boom transmission at long range within the natural habitat of the species, finding that the frequency content of booms was reliably transmitted up to 600 m. Additionally, by testing males' behavioural responses to playbacks of modified signals, we found that the presence of the second harmonic and the frequency modulation are the key parameters for species identification, and also that a sequence of booms elicited stronger responses than a single boom. Thus, the coding–decoding process relies on redundant and propagation-resistant features, making the booms particularly well adapted for the long-range transmission of information between males. Moreover, by experimentally disentangling the presentation of visual and acoustic signals, we showed that during the booming phase of courtship, the two sensory modalities act in synergy. The acoustic component is dominant in the context of intra-sexual competition. While the visual component is not necessary to induce agonistic response, it acts as an amplifier and reduces the time of detection of the signaller. The utilization of these adaptive strategies allows houbara males to maximize the active space of vocalizations emitted in exploded leks.